Zambia Economic Brief, December 2014, Issue 4 : Financial Services - Reaching Every Zambian - World Bank Group (Washington, DC, 2014)
Zambia s economy is estimated to grow around 6.0 percent in 2014, slower than the 6.7 percent in the previous two years. Growth comes from a bumper maize harvest; rapid expansion in the construction industry supported in part by public investment in roads; and continued strong growth in services. Following the large fiscal deficit of 6.6 percent in 2013, the economy experienced turbulence during the first half of the year when the kwacha depreciated sharply against the U.S. dollar and other currencies, and inflation pressure increased. However, in response to policy actions, the kwacha stabilized subsequently and regained about half of the lost value, and inflation pressure also ebbed. Average inflation in 2014 is expected to be around 7.8 percent, higher than the targeted 6.5 percent and the 2013 average of 7.0 percent.